Wear behaviour of powder metallurgy iron composite reinforced with 20wt.% silica particles - Amir, Adibah; Mamat, Othman (Laboratory Soete, Ghent University, 2014)
In an effort to find a cheaper production of particles reinforced metal matrix composite for tribological applications, this study focuses on ferum, which is known as the oldest and cheapest tribological material. Natural silica sand extracted from ex mining land was used as the reinforcement. Study of its wear performance was conducted with ball-on-disk apparatus in dry sliding condition. The effects of sliding distances, rotational speeds, and applied loads on the wear behaviors of the composite were investigated. Examination from Field Emission Scanning Electron Microscopy (FE-SEM) had revealed that the dominant wear mechanism was delamination followed by oxidation and adhesion. Interestingly, reinforcement of SiO2 sand particles has not been beneficial in reducing or delaying wear, instead it had changed the wear behavior of the composite.